2011
DOI: 10.1016/j.supflu.2011.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Selective hydrogenation of nitrostyrene to aminostyrene over Pt/TiO2 catalysts: Effects of pressurized carbon dioxide and catalyst preparation conditions

Abstract: The present work has studied the influence of CO 2 pressurization on the hydrogenation of nitrostyrene (NS) using Pt/TiO 2 . With CO 2 pressurization up to 12 MPa (CO 2 -dissolved expanded liquid (CXL) phase), the over-all reaction rate and the selectivity to aminostyrene (AS) increased. At higher CO 2 pressures where all NB dissolved in scCO 2 (scCO 2 -homogeneous phase), both of them decreased with increasing the CO 2 pressure. The phase behavior was an important factor for the present reaction system. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…Similar FTIR measurements were made for liquid BN dissolving CO 2 at high pressures by ATR mode [31]. Fig.…”
Section: In Situ High-pressure Ftir Measurements (A) Molecular Interasupporting
confidence: 66%
See 2 more Smart Citations
“…Similar FTIR measurements were made for liquid BN dissolving CO 2 at high pressures by ATR mode [31]. Fig.…”
Section: In Situ High-pressure Ftir Measurements (A) Molecular Interasupporting
confidence: 66%
“…In situ high-pressure FTIR was used to examine the interactions between CO 2 and BN molecules in the absence and presence of water using a JASCO FTIR-620 spectrometer with a triglycine sulfate detector at a frequency resolution of 2 cm -1 . The FTIR measurements were made with a home-designed high pressure cell of 1.18 cm 3 attached with a ZnSe rod in attenuated total reflection (ATR) mode [31]. A certain volume of BN was introduced into the cell and it was purged with CO 2 several times.…”
Section: In Situ High-pressure Ftir Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionalized anilines are industrially important intermediates for pharmaceuticals, polymers, herbicides, and other substances and fine chemicals [1][2][3]. The selective reduction of a nitro group when other reducible groups are present in the same molecule is very challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Fujita et al [2] used pressurized CO 2 as the reaction medium and found that higher selectivity to VA was obtained than in its absence at any conversion level. The effect of dense-phase CO 2 was ascribed to retardation on the hydrogenation of vinylaniline (VA) to ethylaniline (EA).…”
Section: Introductionmentioning
confidence: 99%